2009
DOI: 10.1016/j.ijgo.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of radical hysterectomies performed by general gynecologists in Jamaica

Abstract: General gynecologists with significant experience in general gynecologic surgery who underwent adequate, but abbreviated, training became competent in performing a radical hysterectomy, with outcomes comparable to those seen in high-resource countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…These findings are consistent with the broader literature 38–40 . Nevertheless, these results were challenged by another study which showed that GGs with substantial experience in general gynecologic surgery may become competent in performing a modified radical hysterectomy with abridged training, demonstrating outcomes comparable to those measured in high income countries (HICs) 33 . Considering these summed findings, there is a great need to explore the implications of implementing programs providing subspecialized gynecologic oncologic training to GGs and/or GSs.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…These findings are consistent with the broader literature 38–40 . Nevertheless, these results were challenged by another study which showed that GGs with substantial experience in general gynecologic surgery may become competent in performing a modified radical hysterectomy with abridged training, demonstrating outcomes comparable to those measured in high income countries (HICs) 33 . Considering these summed findings, there is a great need to explore the implications of implementing programs providing subspecialized gynecologic oncologic training to GGs and/or GSs.…”
Section: Discussionsupporting
confidence: 74%
“…Five studies (26%) compared differences in patient outcomes for treatment of early‐stage cancer provided by a subspecialized versus a non‐subspecialized surgical provider 31–35 . Notably, only two of these studies included patients with cervical cancer, 31,33 one of which also included patients with endometrial cancer 33 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations